Convergent synthesis and characterization of fatty acid-conjugated poly(ethylene glycol)-block-poly(epsilon-caprolactone) nanoparticles for improved drug delivery to the brain. (January 2018) - Li, Ho Yin; Zhang, Bowen; Chan, Pui Shan; Weng, Jingwen; Tsang, Chi Kwan; Lee, Wai Yip Thomas
Graphical abstract: Highlights: Nine different fatty acid-conjugated PEG-b-PCL nanoparticles were prepared. These nanoparticles are <100 nm with a fairly narrow particle size distribution. These nanoparticles are non-hemolytic and non-cytotoxic. The cargo-loaded nanoparticles exhibit zero-order drug release. Oleic acid-conjugated nanoparticles improve the delivery of the loaded cargo to the brain. Abstract: Herein, for the first time, we report the synthesis, preparation, and characterization of fatty acid-conjugated poly(ethylene glycol)-block-poly(epsilon-caprolactone) nanoparticles (FA-NPs), with the ultimate goal of improving drug delivery to the brain. These nanoparticles had a nano-size (<100 nm) with a fairly narrow size distribution (PDI = 0.2–0.3). They were non-hemolytic and non-cytotoxic. By employing curcumin, a poorly soluble herbal molecule, as a model, FA-NPs enhanced the drug solubility by >5.4 × 10 5 x. They showed moderate stability in serum and exhibited zero-order drug release. As a proof-of-concept, the brain uptake of oleic acid-NPs (OA-NPs) was examined in rats after intravenous injections. Relative to 1% DMSO and PEG-NPs formulations, the OA-NPs enhanced the brain accumulation of the loaded cargo by 4.28 and 1.94x, respectively. Apparently, these nanoparticles hold considerable promise in drug delivery to the brain and their potential applications for disorders of the central nervous system should be explored.